Building A Psychological Profile of Olympic Medalists and World Champions - Nideffer, R. M.; Bond, J.; Cei, A.; Manili, U.
The purpose of the present study was to determine the extent to which those concentration and interpersonal skills measured by The Attentional and Interpersonal Style (TAIS) Inventory, could differentiate between world champion athletes based on the number of medals or world championships they had won (Nideffer, 1976). We searched a TAIS data base of approximately 10,000 elite level athletes, and were able to identify 239 individuals who had won at least one Olympic Medal or world championship. These two hundred and thirty nine athletes were competing in 23 different sports. There were 171 males and 68 females. Combined, these individuals had won 113 Olympic Gold Medals, 44 Olympic Silver Medals, 73 Olympic Bronze Medals and 170 World Championships. For purposes of this study, the subjects were divided into two groups. A multiple medal winners group (N=87) with a mean age of 26.5, that consisted of 69 males and 18 females. A single medal winners group (N=152) with mean age of 23.5, consisting of 102 males and 50 females.